Glial calcium signalling - Verkhratsky, Alexei (Henry Stewart Talks, 2011)
How calcium signalling was discovered, Principles of calcium signalling, Calcium signalling in neuroglia, Voltage- and ligand-gated channels, Endoplasmic reticulum calcium store, Store-operated calcium entry, Calcium signals in neuronal-glial interactions, Glial calcium waves